Analysis of the Application of Value Engineering in Building Project X Kuningan District - Cahyani, Andhiny Gita; Rohaedi, Mochamad Daffa; Nurazizah, Fadia Lutfah; Rozy, Nikko (Indonesian Journal of Advanced Research, 2025)
Construction project efficiency is the key to success amid budget pressures and cost inflation. Value Engineering (VE) is a systematic solution to balance cost, reliability, and project performance. Pareto analysis identified four main works for optimization: walls, frames, floors, and ceilings with cost/worth ratio >1. Alternative solutions included AAC/HEBEL walls, PVC sills, unpolished homogenius tile, and PVC ceiling. The implementation of Value Engineering resulted in significant savings in walls (38.63%), frames (24.21%), ceilings (46.62%), and floors (39.74%). The total savings reached Rp1.481.761.485,10 (38,52% of the initial cost), with Life Cycle Cost as the main consideration.